Polar Bear Distribution and Abundance on the Southwestern Hudson Bay Coast During Open Water Season, in Relation to Population Trends and Annual Ice Patterns - Stirling, Ian; Lunn, N.J.; Iacozza, John; Elliott, Campbell; Obbard, Martyn (ARCTIC, 2004)
In Hudson Bay, all the ice melts in summer, and the last areas to be ice-free (around mid-to-late July) are usually off the coasts of Manitoba and Ontario. Thus, all polar bears are forced ashore to fast until freeze-up in November (ca. four months). Pregnant females remain ashore for eight months. In most years from 1963 through 1997, aerial surveys to monitor polar bear populations were conducted along all or part of the coastline between Cape Churchill, Manitoba, and Cape Henrietta Maria, Ontario, in late August and early September. Satellite data, from which breakup and ice absence times could be estimated, first became available in 1971. The numbers of animals counted were tallied in two subareas within Manitoba and three within Ontario. We evaluated the coastal counts, along with independent data on the movements of tagged bears and annual patterns of ice breakup from 1971 through 1996. We concluded that 1) the coastal survey data reliably indicated the population trends in Manitoba and Ontario; 2) little exchange occurred between the Western Hudson Bay (Manitoba) and Southern Hudson Bay (Ontario) populations; 3) between 1971 and 2001, there was a statistically significant trend toward earlier breakup of sea ice off the Manitoba coast, but not off the Ontario coast; 4) the onset of ice absence along the coast had no significant relationship to the number of bears present in each sub-sampling area within either the Manitoba or the Ontario population, but did significantly influence the distribution of bears on the coastline of each province independently of the other; 5) timing of the surveys can influence the results; and 6) adult male and female bears both showed a high degree of fidelity to specific areas during summer, independent of the pattern of ice breakup. Dans la baie d'Hudson, toute la glace fond en été, et les dernières zones à être non englacées (du milieu à la fin de juillet environ) se trouvent généralement au large des côtes du Manitoba et de l'Ontario. Ainsi, tous les ours polaires sont ...